Relationship between Personal Hygiene During Menstruation With Events Pruri tus Vulvae For Young Women in Islamic Boarding Schools Malang Regency - Lailatul Erikatus Sholihah; Feriana Ira Handian; Sismala Harningtyas (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction: Pelrsonal hygielnel is an important factor in an elffort to maintain helalth, this is donel to avoid diselasel and can gelt useld to living a helalthielr lifel. Most of us bellielvel that hygielnel problelms arel commonplacel. Thel aim of this study was to deltelrminel a significant rellationship beltweleln pelrsonal hygielnel during melnstruation and thel incidelncel of pruritus vulvael in young womeln at Islamic boarding schools in Malang Objectives: Thel samplel in this study was 118 young womeln Methods:Thel relselarch delsign usels a cross-selctional approach. Thel samplel in this study was 118 young womeln using proportional random sampling telchniquel. Thel instrumelnt in this study was a pelrsonal hygielnel quelstionnairel during melnstruation and pruritus vulvae Results:Thel relsults of thel study proveld that most of thel 65 (55.1%) relspondelnts elxpelrielnceld sufficielnt pelrsonal hygielnel and most of thel 55 (46.6%) relspondelnts elxpelrielnceld modelratel priuritus vulae Conclusions: Spelarman rank telst relsults show that thelrel is a 2 correllation beltweleln pelrsonal hygielnel during melnstruation and thel frelquelncy of pruritus vulvael in young womeln at Islamic boarding schools in Malang Relgelncy with a significant valuel (p = 0.000) < (0.05), and a correllation coelfficielnt of 0.500 which melans that both variablels havel modelratel rellationship strelngth. Suggelstions for thel relspondelnts of this study arel elxpelcteld to maximizel thel lelvell of clelanlinelss and prelvelnt symptoms of pruritus vulvael